Adenomas and Carcinomas Missed in Routine Colonoscopy: A Prospective Study in Resected Colon Segments - v. Schönfeld, J.; Hauser, D.; Hartmann, C.-A.; Schroeder, J. (Zeitschrift für Gastroenterologie, 2014)
Colonoscopy is the standard technique in the diagnosis and treatment of colorectal neoplasia, but small adenomas and even advanced lesions can be missed during the procedure. With large scale screening colonoscopy programs installed, information on quality of colonoscopy in primary care is essential, but scarcely available. Over a period of 45 months, we prospectively included all those patients in our study, who underwent major colonic surgery at our institution and who had undergone a colonoscopy within 42 days prior to the operation. 89 men and 100 women, median age 71 years, were included. The majority of these operations were performed for colorectal carcinoma (125), other malignant tumors (4), suspected malignancies (6) or large adenomas (14). The pathologist inspected the resected colonic segment, and we compared his findings with the colonoscopy report. Colonoscopies had been performed by 22 doctors in 13 institutions. Median length of the resected colonic segments was 20 cm (range 3 to 135 cm), total length was 41,21 metres. In 14 segments the pathologist identified 28 neoplastic lesions not described in the endoscopy report. Colonoscopy had missed 2 carcinomas, both in the right colon, and a 12 mm tubulo-villous adenoma with high-grade dysplasia. Another 25 tubular adenomas had been missed, 2 measuring 10 mm, 7 between 5 and 9 mm and 16 smaller than 5 mm. We conclude that primary care colonoscopy misses neoplastic lesions in a significant number of procedures. Most of the missed lesions in our high risk group of patients would have been of little clinical consequence. In a small, but clinically important number of cases, however, advanced adenomas and even colorectal carcinomas were missed by endoscopy.
Keywords: kolorektales Adenom; kolorektales Karzinom; Koloskopie